2018
DOI: 10.1016/j.tsf.2018.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mo1−xNbxS2 thin films by separate-flow chemical vapor deposition with chloride sources

Abstract: The doping of element (Nb, Ta, etc.) into MoS 2 , one of the layered transition metal dichalcogenides, is a key technology for electronic devices because the lack of the p-type MoS 2 has limited the range of applications. We report that the Mo 1-x Nb x S 2 thin films were synthesized on SiO 2 /Si substrates by chemical vapor deposition (CVD). It was critical to use chloride sources (MoCl 5 and NbCl 5) for the synthesis of Mo 1-x Nb x S 2. The Nb concentration can be increased to 10% by controlling the supplied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Transition-metal dichalcogenides (TMDCs) such as MoS 2 and WS 2 are well-known as petrochemical catalysts and as dry lubricants. , Atomically thin crystalline sheets of TMDCs have attracted attention for applications in electronics, valleytronics, and more . Probably, the most attractive aspect of TMDCs as two-dimensional (2D) layered materials is the fact that their cation and anion compositions and hence their functionalities can be controlled. Experimental investigations of TMDC alloys have however largely been limited to two-cation/anion systems with a few exceptions. The concept of entropy-stabilized alloys, now extended to a variety of compounds (borides, carbides, nitrides, , oxides, and quasi-2D MXenes , ), is applicable to TMDCs. Among the TMDCs, alloys with five transition-metals have the highest entropy of mixing (−1.6 RT , where R is the universal gas constant), thereby suggesting an entropically stabilized configuration; density functional theory (DFT) calculations , coupled with experiments of selected group 5 and 6 cation compositions revealed that although some of the ternary alloys are unstable, high-entropy alloy (HEA) TMDCs are stable with superior thermal, electrochemical, and electronic characteristics.…”
mentioning
confidence: 99%
“…Transition-metal dichalcogenides (TMDCs) such as MoS 2 and WS 2 are well-known as petrochemical catalysts and as dry lubricants. , Atomically thin crystalline sheets of TMDCs have attracted attention for applications in electronics, valleytronics, and more . Probably, the most attractive aspect of TMDCs as two-dimensional (2D) layered materials is the fact that their cation and anion compositions and hence their functionalities can be controlled. Experimental investigations of TMDC alloys have however largely been limited to two-cation/anion systems with a few exceptions. The concept of entropy-stabilized alloys, now extended to a variety of compounds (borides, carbides, nitrides, , oxides, and quasi-2D MXenes , ), is applicable to TMDCs. Among the TMDCs, alloys with five transition-metals have the highest entropy of mixing (−1.6 RT , where R is the universal gas constant), thereby suggesting an entropically stabilized configuration; density functional theory (DFT) calculations , coupled with experiments of selected group 5 and 6 cation compositions revealed that although some of the ternary alloys are unstable, high-entropy alloy (HEA) TMDCs are stable with superior thermal, electrochemical, and electronic characteristics.…”
mentioning
confidence: 99%